1993
DOI: 10.1128/jcm.31.12.3090-3095.1993
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis in early Lyme disease

Abstract: Using a commercially available enzyme-linked immunosorbent assay (ELISA) and an immunoblot assay (IB), we tested sera from 100 patients with erythema migrans (EM) seen in 1991 at the Westchester County Medical Center Lyme Disease Diagnostic Center. Convalescent-phase sera were available from 59 patients. Fifty-five patients had EM of <7 days' duration, 31 had EM of 7 to 14 days' duration, and 14 had EM of >14 days' duration. During the acute phase of infection, 35 patients had a positive ELISA result and 43 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 34 publications
5
54
0
Order By: Relevance
“…With a subsequent expansion of the immune response and production of IgG antibodies during later stages of illness, p22, p39, and OspF antigens became more useful in laboratory diagnoses. Antibody reactivities to the p22 and p39 antigens have been found to be important indicators of B. burgdorferi infections (1,2,6,7,16,20,29). Other antigens, such as p35 (47-kDa fibronectin-binding protein) and p93, likewise have been shown to be important markers for early and late Lyme borreliosis, respectively (2, 5-8, 11, 19, 27).…”
Section: Discussionmentioning
confidence: 99%
“…With a subsequent expansion of the immune response and production of IgG antibodies during later stages of illness, p22, p39, and OspF antigens became more useful in laboratory diagnoses. Antibody reactivities to the p22 and p39 antigens have been found to be important indicators of B. burgdorferi infections (1,2,6,7,16,20,29). Other antigens, such as p35 (47-kDa fibronectin-binding protein) and p93, likewise have been shown to be important markers for early and late Lyme borreliosis, respectively (2, 5-8, 11, 19, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Also important besides strain analysis are the implications of OspC heterogeneity for diagnostic tests and immunoprophylaxis. OspC has been recognized as an immunodominant antigen for the IgM immunoresponse in European (37) as well as North American (9) patients and is the earliest antigen detected by Western blot in sera from patients with erythema migrans (1).…”
Section: Discussionmentioning
confidence: 99%
“…False-positive reactions by enzyme-linked immunosorbent assay (ELISA) have been detected by the use of Western immunoblots (IBs) (10,12,15). Furthermore, we and others have found immunoglobulin M (IgM) IBs to be of greater sensitivity than polyvalent ELISAs in patients with early Lyme disease of short duration (1,15,17). Mitchell et al (23) reported on the serology of patients with culture-confirmed erythema migrans (EM) in a comparison of four commercial immunoassays and found that an IgM immunofluorescence assay has the highest sensitivity, but the results of an evaluation of an IgM IB kit were not presented.…”
mentioning
confidence: 99%